2012
DOI: 10.1146/annurev-biochem-052610-095910
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase II Elongation Control

Abstract: Regulation of the elongation phase of transcription by RNA Polymerase II (Pol II) is utilized extensively to generate the pattern of mRNAs needed to specify cell types and to respond to environmental changes. After Pol II initiates, negative elongation factors cause it to pause in a promoter proximal position. These polymerases are poised to respond to the positive transcription elongation factor, P-TEFb, and then enter productive elongation only under the appropriate set of signals to generate full length pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
638
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 525 publications
(654 citation statements)
references
References 175 publications
(238 reference statements)
7
638
1
8
Order By: Relevance
“…After transcription initiation, RNA Pol II is trapped near the promoter of many genes, a process known as proximal promoter pausing (Core et al 2008;Zhou et al 2012;Lee and Young 2013). For productive transcription, P-TEFb is recruited, and CDK9 phosphorylates Ser2 in the C-terminal domain (CTD) of RNA Pol II, inducing pause release and subsequent transcription elongation (Zhou et al 2012;Lee and Young 2013).…”
Section: Cdk9 Mediates Transcription Elongation Of Myc Targets In Mycmentioning
confidence: 99%
See 1 more Smart Citation
“…After transcription initiation, RNA Pol II is trapped near the promoter of many genes, a process known as proximal promoter pausing (Core et al 2008;Zhou et al 2012;Lee and Young 2013). For productive transcription, P-TEFb is recruited, and CDK9 phosphorylates Ser2 in the C-terminal domain (CTD) of RNA Pol II, inducing pause release and subsequent transcription elongation (Zhou et al 2012;Lee and Young 2013).…”
Section: Cdk9 Mediates Transcription Elongation Of Myc Targets In Mycmentioning
confidence: 99%
“…For productive transcription, P-TEFb is recruited, and CDK9 phosphorylates Ser2 in the C-terminal domain (CTD) of RNA Pol II, inducing pause release and subsequent transcription elongation (Zhou et al 2012;Lee and Young 2013). MYC has previously been shown to participate in transcription elongation by regulating this pause release mechanism (Eberhardy and Farnham 2001;Kanazawa et al 2003;Rahl et al 2010).…”
Section: Cdk9 Mediates Transcription Elongation Of Myc Targets In Mycmentioning
confidence: 99%
“…When an SEC is recruited to the HIV promoter by Tat and TAR, the contained P-TEFb and ELL1/2 components potentially can act on the same polymerase enzyme to activate transcription synergistically (10). However, direct biochemical evidence still is needed to confirm that P-TEFb alone is not sufficient for full Tat activity and that efficient HIV transactivation must rely on the complete SEC.In addition to residing in the SEC, P-TEFb also exists in several other complexes and shuttles between inactive and active states in response to different intracellular and extracellular signals (5,7,8). Under normal conditions, most nuclear P-TEFb Significance Transcriptional elongation by RNA polymerase II produces fulllength RNA transcripts and plays a general and prominent role in regulating gene expression.…”
mentioning
confidence: 99%
“…Since 2007, however, accumulating evidence has revealed that promoter-proximal pausing of Pol II during early elongation is much more prevalent than previously thought, suggesting that intricate control of gene expression can occur frequently at this stage also (3,4). Indeed, the importance of controlled pause and release of Pol II is illustrated by the observations that this process plays a prominent role in regulating cell growth, renewal, and differentiation (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation